Biometric authentication using fingerprint and keypad for door lock securtiy system - Al-Azam, Sharaf Ahmed; Sarea, Hammed; Sulong, Muhammad Suhaimi (Middle East International Journal For Social Sciences, 2021)
Biometric lock is a lock that uses fingerprint to grant genuine user an access to a building, offices, and laboratory. The purpose of this project is to solve the major problems faced by the conventional lock or electronic combination lock, by adding electronic technology as well as biological technology together, user is the key to the lock. Users do not have to memorize combination as it is in the electronic combination lock, or carry the key along all the time. However with this device users simply need to place their finger on the fingerprint module and the device itself will determine whether to give or deny the access. This study also has other method which is password by using keypad. This study divided into three parts, which are hardware design, software design, and prototype design. The hardware design includes the electronics circuits used to enrol, identify, and delete fingerprint to the fingerprint module, LCD that gives command to the user. Software design includes the development of the source code that enables the Arduino UNO to control and interface with all hardware. The operation of the hardware, software and prototype design parts have been tested and verified individually and in combination. It simply performs three functions which are addition, verification, and deletion.